Influences of age and sex on the diagnostic accuracy of human epididymis secretory protein 4 for malignant pleural effusion - Qian Yang; Yan Niu; Qianghua Zhou; Dan-Ni Yang; Hong-Zhe Zhu; Cheng Yan; Su-Na Cha; Ting-Wang Jiang; Li Yan; Wen-Qi Zheng; Jian-Xun Wen; Zhi-De Hu (Scientific Reports)
Abstract Previous studies have suggested that the presence of human epididymal protein 4 (HE4) in pleural fluid can be used to diagnose malignant pleural effusion (MPE) with moderate accuracy. However, the factors that affect the diagnostic accuracy of HE4 remain unknown. This study aimed to examine how age and sex influence the diagnostic accuracy of HE4. Participants with undiagnosed pleural effusion were prospectively enrolled in two cohorts (Hohhot cohort and Changshu cohort), and the presence of HE4 in their pleural fluid upon admission was determined by an electrochemiluminescence immunoassay. A receiver operating characteristic (ROC) curve with its area under the curve (AUC) was utilized to assess the diagnostic value of HE4 for MPE. Additionally, we conducted subgroup analyses and used a resampling method with different upper age limits to investigate the impacts of age and sex on the diagnostic accuracy of HE4 for MPE. The Hohhot cohort included 86 patients with benign pleural effusions (BPEs) and 66 patients with MPE, whereas the Changshu cohort included 26 patients with MPE and 32 patients with BPE. The diagnostic accuracy of HE4 decreased as age increased in both cohorts. The diagnostic accuracy of HE4 in males did not differ significantly from that in females. Therefore, we conclude that age should be considered when using HE4 in pleural fluid to diagnose MPE.